2010
DOI: 10.1037/a0019013
|View full text |Cite
|
Sign up to set email alerts
|

Is it beneficial to have an Alcoholics Anonymous sponsor?

Abstract: Alcoholics Anonymous (AA) attendance is predictive of increased abstinence for many problem drinkers and treatment referral to AA is common. Strong encouragement to acquire an AA sponsor is likewise typical, and findings about the benefits associated with social support for abstinence in AA support this practice, at least indirectly. In spite of this widespread practice, however, prospective tests of the unique contribution of having an AA sponsor are lacking. This prospective study investigated the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
70
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 40 publications
6
70
1
Order By: Relevance
“…Although these approaches may enable evaluation of the effectiveness of 12-step programs in attenuating all alcohol and drug use, they obscure possibly important temporal interactions between use of different classes of substances. For example, Tonigan and Rice (2010) found that 41% of an AA-recruited sample reported being abstinent from alcohol use at their 6-month follow-up interviews. However, a smaller percentage of the sample (31%) was abstinent from use of alcohol, marijuana, and cocaine during the same follow-up period.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Although these approaches may enable evaluation of the effectiveness of 12-step programs in attenuating all alcohol and drug use, they obscure possibly important temporal interactions between use of different classes of substances. For example, Tonigan and Rice (2010) found that 41% of an AA-recruited sample reported being abstinent from alcohol use at their 6-month follow-up interviews. However, a smaller percentage of the sample (31%) was abstinent from use of alcohol, marijuana, and cocaine during the same follow-up period.…”
mentioning
confidence: 99%
“…This is potentially an important benefi t of such programs, given the increasing prevalence of polysubstance use disorders over the past 2 decades (Griffi n et al, 2009). Along these lines, it is estimated that 64% of alcoholics also use illicit drugs (Tsuang et al, 1994), including marijuana (42%), cocaine (34%), and opioid drugs (20%), among others (Tonigan and Rice, 2010). Furthermore, roughly 50% of all alcoholics suffer from comorbid illicit substance use disorders (Ross, 1993), an estimate that is consistent with the comorbidity rate reported in the Alcoholics Anonymous Triennial Survey (1990).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To control for prior learning effects when investigating change processes, the parent study excluded adults who had prior success at achieving abstinence (Tonigan and Beatty, 2011;Tonigan and Rice, 2010). Thus, participants were excluded from the study if they had already achieved alcohol abstinence for 12 months or longer or had attended AA for more than 4 months.…”
Section: Participantsmentioning
confidence: 99%